Understanding the Physical Principles of Doppler Ultrasound (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
The results showed that Grey Doppler and Color Doppler produce very different images and cannot diagnose the same things. Color Doppler ultrasound captures changes in blood flow more clearly and accurately than grayscale imaging, enabling doctors to diagnose artery problems more accurately. Both types of medical imaging showed the anatomy, blood flow patterns in the cyst, and arterial dilatation correctly.Materials and MethodThe Doppler examination is performed in the same way as a regular ultrasound, where after applying the gel to the area with a deep pen diluted on the area, the ultrasound examiner moves it or moves it until the doctor detects the signal well. It should start to move less noticeably, and then sounds that represent blood flow in the blood vessels are heard.  Results     The study found that Grey Doppler and Colour Doppler performed differently in problem diagnosis and photo quality. Colour Doppler ultrasonography displayed blood flow dynamics more accurately and precisely than greyscale imaging, enabling more accurate vascular abnormality detection. In medical imaging, both modalities precisely reconstruct anatomical features, cyst blood flow patterns, and artery dilations. Color Doppler ultrasound's clarity and detail in monitoring blood flow distribution in vessels improved the diagnosis's accuracy.ConclusionsUsing physical technology to enhance the accuracy and understanding of medical images, Doppler ultrasound has been investigated in advanced clinical settings such as diagnosing cardiovascular disorders and has been found to be highly accurate in diagnosis.